The Life and Work of Muhammadjon Kholbekov, Literary Critic and Translator - Mamadazizova Shaxnoza (Zien Journals, 2022)
This article provides information on the work done in Uzbekistan in the field of translation studies, as well as on the work and activities of the literary critic Kholbekov Muhammadjon
Keywords: Literary critic; translator; theory of translation; history of translation